Catechol derivative coordinated TiO2 and metal phthalocyanine photo-anode material as well as preparation method and application thereof

By designing the TiO2@ metal phthalocyanine photoanode material for catechol derivative coordination, using the core-shell structure to improve carrier transmission, the problem of insufficient selectivity and catalytic activity of glycerol oxidized glyceraldehyde in the prior art was solved, and the Efficient photoelectric catalytic conversion provides a green and efficient upgrade transformation path for the biodiesel industry.

CN119194506AActive Publication Date: 2024-12-27ZHEJIANG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411062241.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-27
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

The existing photoelectric catalytic technology is difficult to achieve high selectivity and efficient conversion to glyceraldehyde in the process of oxidizing glycerol, and traditional photoanode materials have shortcomings in carrier transport and catalytic activity, which affects the development of the biodiesel industry.

Method used

A TiO2@ metal phthalocyanine photoanode material with catechol derivative coordination was designed, and the core-shell structure of nanorod array structure was prepared by hydrothermal reaction and solvothermal method was used to bridge TiO2 with metal. Phthalocyanine improves carrier transport performance, improves catalytic activity and product selectivity.

Benefits of technology

The efficient conversion of glycerol into glyceraldehyde has been achieved, the photocurrent density and yield has been improved, the problem of C-C bond fracture during the oxidation of multi-carbon organic matter has been alleviated, and a green and efficient upgrade conversion path is provided for the biodiesel industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004978279190000011
    Figure HDA0004978279190000011
  • Figure HDA0004978279190000012
    Figure HDA0004978279190000012
  • Figure HDA0004978279190000021
    Figure HDA0004978279190000021
Patent Text Reader

Abstract

The invention discloses a catechol derivative coordinated TiO2 and metal phthalocyanine photo-anode material and a preparation method and application thereof.The material takes a TiO2 nano array as a core, a catechol derivative coordination agent as a bridge and metal phthalocyanine as a shell to form a coordination agent bridged core-shell structure, and the material can be used in a reaction for synthesizing glyceraldehyde through photoelectrocatalysis selective oxidation of glycerin; according to the material, the separation efficiency of photon-generated carriers is effectively improved, then the photoelectrocatalytic activity of glycerin is remarkably improved, biomass oriented upgrading of converting glycerin into glyceraldehyde is achieved, meanwhile, the photoelectrocatalytic reaction condition is mild, the problem of C-C bond breakage in the oxidation process of multi-carbon organic matter can be effectively solved, and the method is suitable for industrial production. A new thought is provided for high-selectivity preparation of multi-carbon products, and the method has very important significance on green development of the biodiesel industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photoelectrocatalytic materials and organic synthesis, and in particular to a catechol derivative-coordinated TiO2@metal phthalocyanine photoanode material with a core-shell structure and a preparation method thereof, as well as application in photoelectrocatalytic oxidation of glycerol into glyceraldehyde. Background Art

[0002] Photoelectrocatalysis (PEC) is currently a powerful strategy that combines the advantages of photocatalysis and electrocatalysis. It can achieve efficient charge separation with the help of lower bias voltage, while saving energy, avoiding over-oxidation of reaction substrates, reducing side reactions, and achieving higher selectivity. Glycerol, as the main by-product in the production of biodiesel, can be mildly converted into C3 value-added chemicals such as glyceraldehyde and 1,3-dihydroxyacetone (DHA) through the strategy of photoelectrocatalytic oxidation to achieve biomass upgrading. Among them, glyceraldehyde has a wide range of application value and is often used as a nutritional supplement, food preservative and pharmaceutical intermediate. Therefore, the rational design and preparation of efficient and stable photoanode materials for photoelectrocatalytic oxidation of glycerol to glyceraldehyde is of great significance to the development of the biodiesel industry.

[0003] Metal phthalocyanine is an organic compound composed of a planar macrocycle and a central metal ion. It exhibits good catalytic activity in many reactions. The electronic structure of metal phthalocyanine can be effectively adjusted by coordinating the metal center of the metal phthalocyanine with a ligand. The catechol derivatives with bidirectional coordination function can not only adjust the electronic structure of metal phthalocyanine, but also improve the carrier transport performance between the semiconductor catalyst and the metal phthalocyanine by bridging the oxide semiconductor at the other end, realize the bidirectional coordination of the core-shell structure, improve the PEC performance, and show better catalytic activity and product selectivity. Therefore, the rational design of the core-shell structure bridged by the ligand is used for the photoelectrocatalytic oxidation of glycerol to selectively generate glyceraldehyde, which is a valuable photoanode design and preparation strategy. Summary of the invention

[0004] The invention provides a TiO2@metal phthalocyanine photoanode material coordinated by a catechol derivative and a preparation method thereof. The material can be used for photoelectrocatalytic oxidation of glycerol into glyceraldehyde, thereby realizing directional upgrading and conversion of biomass.

[0005] The technical solution of the present invention is as follows:

[0006] A catechol derivative coordinated TiO2@metal phthalocyanine photoanode material, with TiO2 nanoarray as core, coordination agent as bridge, and metal phthalocyanine as shell, forming a coordination agent bridged core-shell structure;

[0007] Preferably, the TiO2 nanoarray is a nanorod array structure, and the diameter of the nanorods is 80 to 150 nm;

[0008] The ligand is a catechol derivative selected from: 3,4-dihydroxybenzonitrile, dopamine or caffeic acid;

[0009] The metal phthalocyanine is a single metal or multi-metal phthalocyanine selected from: copper phthalocyanine (CuPc), iron phthalocyanine (FePc), cobalt phthalocyanine (CoPc), copper cobalt phthalocyanine (CuCoPc), copper zinc phthalocyanine (CuZnPc), copper iron phthalocyanine (CuFePc) or cobalt iron phthalocyanine (CoFePc);

[0010] The thickness of the metal phthalocyanine shell is 5 to 15 nm.

[0011] The method for preparing the catechol derivative coordinated TiO2@metal phthalocyanine photoanode material of the present invention comprises the following steps:

[0012] (1) Preparation of TiO2 nanoarrays by hydrothermal reaction-calcination method;

[0013] (2) soaking the TiO2 nanoarray obtained in step (1) in an ethanol solution of a catechol derivative at a constant temperature of 20 to 50° C. for 2 to 5 hours to obtain a TiO2 nanoarray coordinated and modified by a catechol derivative;

[0014] The concentration of the ethanol solution of the catechol derivative is 0.1 to 0.5 mg / mL, preferably 0.25 mg / mL;

[0015] The preferred constant temperature soaking temperature is 30°C and the time is 2h;

[0016] (3) placing the catechol derivative coordinated TiO2 nanoarray obtained in step (2) in an ethanol solution of metal phthalocyanine, and performing a solvothermal reaction at 100-150° C. for 3-12 hours to obtain the catechol derivative coordinated TiO2@metal phthalocyanine photoanode material;

[0017] The concentration of the metal phthalocyanine ethanol solution is 1 to 5 mg / mL, preferably 1 mg / mL;

[0018] The preferred solvothermal reaction temperature is 120° C. and the time is 6 h.

[0019] Specifically, the TiO2 nanoarray in the present invention has a nanorod array structure, and its preparation process is as follows:

[0020] Deionized water, concentrated hydrochloric acid (36.5-38 wt%), and tetrabutyl titanate were mixed in an autoclave, added to a cleaned FTO substrate with the conductive surface facing downward, heated to 150°C for hydrothermal reaction for 5 hours, then taken out for rinsing and drying, heated to 450°C in air at a rate of 2°C / min, and kept warm for 30 minutes to obtain a TiO2 nanoarray grown on the FTO substrate;

[0021] Preferably, the volume ratio of deionized water, concentrated hydrochloric acid and tetrabutyl titanate is 3:3:0.1.

[0022] The preparation method of metal phthalocyanine in the present invention is as follows:

[0023] Mix pyromellitic anhydride, phthalic anhydride, urea, ammonium chloride, ammonium molybdate and copper acetate and grind them evenly, place the mixture in a muffle furnace, heat it to 220°C at a rate of 3°C / min, keep it warm for 3 hours, then cool it to room temperature, wash it, and vacuum dry it to obtain copper phthalocyanine (CuPc) in powder form;

[0024] Preferably, the mass molar ratio of pyromellitic anhydride, phthalic anhydride, urea, ammonium chloride, ammonium molybdate, and copper acetate is 0.6098 g: 0.4740 g: 2.721 g: 0.6419 g: 1.1 mmol;

[0025] The preparation method of iron phthalocyanine (FePc) and cobalt phthalocyanine (CoPc) is the same as above, except that copper acetate is replaced by ferric chloride or cobalt chloride;

[0026] The preparation methods of copper cobalt phthalocyanine (CuCoPc), copper zinc phthalocyanine (CuZnPc), copper iron phthalocyanine (CuFePc), and cobalt iron phthalocyanine (CoFePc) are the same as those described above, except that copper acetate is replaced by the corresponding bimetallic chloride.

[0027] The catechol derivative coordinated TiO2@metal phthalocyanine photoanode material of the present invention can be used in the photoelectrocatalytic oxidation reaction of glycerol into glyceraldehyde. The specific application method is as follows:

[0028] An H-type electrolytic cell with a quartz window on one side was used, and the cathode and anode chambers were separated by a Nafion 117 proton exchange membrane. A photoelectrocatalytic reaction system was assembled using TiO2@metal phthalocyanine photoanode material coordinated by a catechol derivative as a photoanode, platinum as a cathode, Ag / AgCl as a reference electrode, and sodium sulfate aqueous solution as an electrolyte. Glycerol was added to the electrolyte in the anode chamber, and the light source was a xenon lamp (300W) equipped with an AM1.5G filter to simulate sunlight, which was irradiated on the photoanode through the quartz window, and a constant voltage was applied for electrolysis to selectively convert glycerol into glyceraldehyde.

[0029] The electrolyte sodium sulfate aqueous solution has a concentration of 0.1 to 1 M, preferably 0.5 M;

[0030] The glycerol concentration in the electrolyte of the anode chamber is 10-100 mM, preferably 100 mM;

[0031] The electrolysis potential is 0.8 to 1.2 V vs. RHE, preferably 1.0 V vs. RHE.

[0032] The beneficial effects of the present invention are:

[0033] The present invention provides a catechol derivative coordinated TiO2@metal phthalocyanine photoanode material, which is bridged by catechol derivative coordination to obtain a core-shell structure in a solvothermal manner. Compared with the traditional method, the microscopic morphology structure of the composite photoanode material is more effectively controlled by adjusting the functional groups on the catechol derivative, and a unique core-shell structure is obtained, which is conducive to improving the carrier transport behavior between the semiconductor and the metal phthalocyanine, improving the hole utilization rate, and thus improving the photoelectrocatalytic activity of glycerol.

[0034] At 1.0 V vs RHE, the photocurrent densities of TiO2@CuPc and TiO2@CuCoPc are 1.75 mA / cm 2 and 1.70mA / cm 2 , which is 3.2 times that of TiO2; the yield of glyceraldehyde on TiO2@CuPc is 113.6mmol / m 2 / h, which is 2.4 times that of TiO2. The present invention realizes the directional upgrading of biomass from glycerol to glyceraldehyde, which can effectively alleviate the problem of CC bond breakage during the oxidation of multi-carbon organic matter and provide a new idea for the highly selective preparation of multi-carbon products. At the same time, the photoelectrocatalytic reaction conditions are mild, which is of great significance to the green development of the biodiesel industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 : Transmission electron microscopy image of the TiO2@CuPc photoanode with core-shell structure in Example 1.

[0036] Figure 2 : Linear sweep voltammogram of TiO2@CuPc photoanode coordinated and bridged with different catechol derivatives in Example 2 in glycerol.

[0037] Figure 3 : The yield diagram of the product glyceraldehyde in Example 2.

[0038] Figure 4 : Linear sweep voltammogram of TiO2@CuCoPc photoanode in glycerol in Example 3. DETAILED DESCRIPTION

[0039] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with specific embodiments, which are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0040] In the following embodiments,

[0041] The preparation process of TiO2 nanoarray is as follows:

[0042] 3 mL of deionized water and 3 mL of concentrated hydrochloric acid were stirred and mixed in a Teflon-lined stainless steel autoclave (volume 25 mL), and then 100 μL of tetrabutyl titanate was added. The cleaned FTO substrate was added with the conductive side facing down and hydrothermally reacted at 150 °C for 5 h. After synthesis, it was rinsed with deionized water and then dried in air. Finally, the sample was heated in air at 2 °C min -1 The TiO2 nanoarrays were obtained by heating the sample to 450°C at a rate of 1000 ℃ and keeping the sample at 450°C for 30 min.

[0043] The preparation method of metal phthalocyanine is as follows:

[0044] 0.6098 g of pyromellitic anhydride, 0.4740 g of phthalic anhydride, 2.721 g of urea, 0.6419 g of ammonium chloride, 0.0034 g of ammonium molybdate, and 0.2196 g of copper acetate (1.1 mmol) were mixed and ground, and the mixture was heated in a muffle furnace at 3 °C min -1 The temperature was raised to 220°C and kept for 3 hours. After the heating was completed, the mixture was cooled to room temperature, washed with deionized water, acetone and ethanol for 3 times, and vacuum dried at 60°C for 12 hours to obtain copper phthalocyanine (CuPc) powder.

[0045] The preparation methods of iron phthalocyanine (FePc) and cobalt phthalocyanine (CoPc) are the same, except that copper acetate is replaced with 1.1 mmol of ferric chloride or cobalt chloride.

[0046] Copper cobalt phthalocyanine (CuCoPc), copper zinc phthalocyanine (CuZnPc), copper iron phthalocyanine (CuFePc), and cobalt iron phthalocyanine (CoFePc) were prepared by adding 1.1 mmol of a double metal chloride, respectively.

[0047] Example 1

[0048] The preparation method of TiO2@CuPc-DHBN photoanode material coordinated by 3,4-dihydroxybenzonitrile is as follows:

[0049] (1) Dissolve 5 mg of 3,4-dihydroxybenzonitrile (DHBN) in 10 mL of ethanol, place in a TiO2 nanoarray, and place in a water bath at 30°C for 2 h to obtain TiO2 coordinated with 3,4-dihydroxybenzonitrile.

[0050] (2) After ultrasonically dispersing 20 mg of copper phthalocyanine with 10 mL of ethanol, the coordinated TiO2 nanoarray was placed in the solution and subjected to a solvothermal reaction at 120°C for 6 h. After the reaction, the excess metal phthalocyanine on the surface was rinsed with ethanol and then dried in air to obtain a TiO2@CuPc photoanode material with a core-shell structure.

[0051] Figure 1This is the transmission electron micrograph of the prepared TiO2@CuPc photoanode. An obvious core-shell structure can be seen from the figure. The diameter of TiO2 is 85nm and the thickness of the shell is 13nm.

[0052] An H-type electrolytic cell with a quartz window on one side was used, 0.5M sodium sulfate aqueous solution was added, and 100mM glycerol was added to the anode chamber. TiO2@CuPc was used as the photoanode, platinum as the cathode, and Ag / AgCl as the reference electrode. The xenon lamp light source was turned on and irradiated through the quartz window on the back of the FTO loaded with the photoanode material. A 1.0V bias was applied for electrolysis for 1h. After the reaction was completed, 1mL of the reaction solution was taken and the product was detected by high performance liquid chromatography. The comparison results showed that the yield of glyceraldehyde on the TiO2@CuPc photoanode was 113.6mmol / m 2 / h, which is 2.4 times that of TiO2.

[0053] Example 2

[0054] The preparation of TiO2@CuPc with a core-shell structure is carried out in the same manner as in Example 1, except that the ligand is changed from 3,4-dihydroxybenzonitrile to dopamine (DA) or caffeic acid (CA), and the obtained composite photoanode material is TiO2@CuPc-DA or TiO2@CuPc-CA.

[0055] Linear voltammetric sweep test was performed in the range of 0.2V to 1.8V vs RHE, such as Figure 2 As shown in Figure 2, the photocurrent density of the TiO2@CuPc photoanode materials with three different catechol derivatives coordinated and bridged is higher than that of TiO2. The best one is TiO2@CuPc-DHBN, with a photocurrent density of 1.75 mA / cm at 1.0 V vs. RHE. 2 , is TiO2 (0.54mA / cm 2 ) is ~3.2 times.

[0056] Performance of three catechol-bridged TiO2@CuPc photoanode materials in photoelectrocatalytic glycerol oxidation reaction Figure 3 As shown, the best one is TiO2@CuPc-DHBN with a yield of 113.6mmol / m 2 / h, is TiO2 (46.6mmol / m 2 / h) is 2.4 times.

[0057] Example 3

[0058] The core-shell structure TiO2@CuCoPc was prepared by the same operation steps as in Example 1. Only 1.1 mmol of cobalt chloride was added during the preparation of monometallic copper phthalocyanine to form bimetallic copper-cobalt phthalocyanine. The other conditions remained unchanged. The cyclic voltammetry curve is shown in Figure 4 As shown in Figure 2, the photocurrent density of TiO2@CuCoPc is higher than that of TiO2, and the photocurrent density at 1.0 V vs. RHE is 1.7 mA / cm 2 , which is ~3.2 times that of TiO2.

Claims

1. A catechol derivative coordinated TiO2@metal phthalocyanine photoanode material, characterized in that: The material uses TiO2 nanoarray as core, coordination agent as bridge, and metal phthalocyanine as shell, forming a coordination agent-bridged core-shell structure. The complexing agent is a catechol derivative; The metal phthalocyanine is a monometallic or polymetallic phthalocyanine.

2. The catechol derivative coordinated TiO2@metal phthalocyanine photoanode material according to claim 1, characterized in that: The complexing agent is selected from: 3,4-dihydroxybenzonitrile, dopamine or caffeic acid.

3. The catechol derivative coordinated TiO2@metal phthalocyanine photoanode material according to claim 1, characterized in that: The metal phthalocyanine is selected from the group consisting of copper phthalocyanine, iron phthalocyanine, cobalt phthalocyanine, copper cobalt phthalocyanine, copper zinc phthalocyanine, copper iron phthalocyanine or cobalt iron phthalocyanine.

4. The method for preparing the TiO2@metal phthalocyanine photoanode material coordinated by a catechol derivative as claimed in claim 1, characterized in that: The steps include: (1) Preparation of TiO2 nanoarrays by hydrothermal reaction-calcination method; (2) soaking the TiO2 nanoarray obtained in step (1) in an ethanol solution of a catechol derivative at a constant temperature of 20 to 50° C. for 2 to 5 hours to obtain a TiO2 nanoarray coordinated and modified by a catechol derivative; (3) Placing the catechol derivative-coordinated modified TiO2 nanoarray obtained in step (2) in an ethanol solution of metal phthalocyanine, and subjecting the solution to a solvothermal reaction at 100-150° C. for 3-12 hours to obtain the catechol derivative-coordinated TiO2@metal phthalocyanine photoanode material.

5. The preparation method according to claim 4, characterized in that: The operation process of step (1) is as follows: Deionized water, concentrated hydrochloric acid and tetrabutyl titanate were mixed in an autoclave, and the cleaned FTO substrate was added with the conductive surface facing down. The temperature was raised to 150°C for hydrothermal reaction for 5 hours, and then the substrate was taken out, rinsed, and dried. It was heated to 450°C in air at a rate of 2°C / min and kept warm for 30 minutes to obtain a TiO2 nanoarray grown on the FTO substrate.

6. The preparation method according to claim 4, characterized in that: In step (2), the concentration of the ethanol solution of the catechol derivative is 0.1 to 0.5 mg / mL.

7. The preparation method according to claim 4, characterized in that: In step (3), the concentration of the metal phthalocyanine ethanol solution is 1 to 5 mg / mL.

8. The preparation method according to claim 4, characterized in that: In step (3), the preparation method of metal phthalocyanine is as follows: Mix pyromellitic anhydride, phthalic anhydride, urea, ammonium chloride, ammonium molybdate and copper acetate and grind them evenly, place the mixture in a muffle furnace, heat it to 220°C at a rate of 3°C / min, keep it warm for 3 hours, then cool it to room temperature, wash it, and vacuum dry it to obtain copper phthalocyanine; The preparation method of iron phthalocyanine and cobalt phthalocyanine is the same as above, except that copper acetate is replaced by iron chloride or cobalt chloride; The preparation methods of copper-cobalt phthalocyanine, copper-zinc phthalocyanine, copper-iron phthalocyanine and cobalt-iron phthalocyanine are the same as above, except that copper acetate is replaced by the corresponding bimetallic chloride.

9. Use of the TiO2@metal phthalocyanine photoanode material coordinated by a catechol derivative as claimed in claim 1 in the reaction of photoelectrocatalytic oxidation of glycerol into glyceraldehyde.

10. The use according to claim 9, characterized in that The application method is as follows: An H-type electrolytic cell with a quartz window on one side was used, and the cathode and anode chambers were separated by a Nafion 117 proton exchange membrane. A photoelectrocatalytic reaction system was assembled using TiO2@metal phthalocyanine photoanode material coordinated by a catechol derivative as a photoanode, platinum as a cathode, Ag / AgCl as a reference electrode, and a sodium sulfate aqueous solution as an electrolyte. Glycerol was added to the electrolyte in the anode chamber, and the light source was a xenon lamp equipped with an AM1.5G filter to simulate sunlight, which was irradiated on the photoanode through the quartz window. A constant voltage was applied for electrolysis to selectively convert glycerol into glyceraldehyde. The electrolyte sodium sulfate aqueous solution concentration is 0.1 to 1M; The glycerol concentration in the electrolyte of the anode chamber is 10-100 mM; Electrolysis potential 0.8~1.2V vs.RHE.

Citation Information

Patent Citations

  • A preparation method of a highly dispersive copper phthalocyanine photoelectric material

    CN109103332A

  • Polydopamine sensitized spacing type titanium dioxide composite film photo-anode and preparation method and application thereof

    CN114182263A

  • Core-shell structure bismuth vanadate and cobalt phthalocyanine composite photoelectrode and preparation method and application thereof

    CN117127212A